2011
DOI: 10.2135/cropsci2010.05.0271
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stubble Height and Cutting Frequency on Regrowth of Berseem Clover in a Mediterranean Semiarid Environment

Abstract: Defoliation management of forage crops affects endogenous reserves (in the root and in the stubble), the residual leaf area, and, consequently, the regrowth and biomass yield. The aim of this study was to evaluate the effect of cutting frequency (28-d vs. 35-d intervals) and stubble height (3 vs. 6 cm) on forage yield, regrowth, and persistence of berseem clover {Trifolium alexandrinum L.). Neither cutting interval nor cutting height affected plant survival during the crop cycle. Frequent clipping reduced cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 30 publications
3
23
0
Order By: Relevance
“…On the whole, when berseem clover did not experience WS (i.e., in WW treatments), aboveground biomass production was about 12 Mg dry matter ha –1 ; this is similar to the biomass obtained in the same environment when rainfall during the growing season was 30% higher than the long-term average [12], [20]. On average, no differences between –AM and +AM conditions were observed in terms of total aboveground biomass production (11.7 vs. 12.0 Mg dry matter ha –1 , calculated as a sum of C1+C2+R28 in WW treatments).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…On the whole, when berseem clover did not experience WS (i.e., in WW treatments), aboveground biomass production was about 12 Mg dry matter ha –1 ; this is similar to the biomass obtained in the same environment when rainfall during the growing season was 30% higher than the long-term average [12], [20]. On average, no differences between –AM and +AM conditions were observed in terms of total aboveground biomass production (11.7 vs. 12.0 Mg dry matter ha –1 , calculated as a sum of C1+C2+R28 in WW treatments).…”
Section: Discussionsupporting
confidence: 76%
“…In Mediterranean areas, it is usually sown in the autumn and grown until early summer as a multicut forage species, thanks to its ability to regrow after cutting [12]. However, during the spring, plant regrowth is often limited by water deficiency, which negatively affects photosynthesis and symbiotic N 2 fixation and leads to a reduction in accumulation and quality of biomass.…”
Section: Introductionmentioning
confidence: 99%
“…So the farmer usually harvests the forage from later summer to early winter in order to gain the maximal yield and quality,and this is the best time for making hay of Songnen grassland because of the good weather, and the height of the remaining stubble usually is 4 -5 cm [5]. But different cutting dates may not only effect on the grass regrowth, and biomass at the current year [17] [18] [19], but also effect on the turning green date, biomass, layering distribution of the biomass for the next year [11] [14] [20]. Previous studies have showed that all the cutting dates run through the whole growing season, such as moderate levels of spring defoliation could improve winter range forage quality [21], cutting in May or June decreased vegetative tillers, but increased crude protein content and in vitro dry digestibility [22], autumn harvest date gained different quality forage [13], winter cutting or grazing didn't affect the spring ground or spring forage yield if it was accomplished before spring growth [23].…”
mentioning
confidence: 99%
“…Fulkerson and Slack (2003) reported that perennial ryegrass (Lolium perenne) defoliated to 20 or 50 mm height in winter yielded 21% more DM than when defoliated to 120 mm. In contrast, Giambalvo, Amato, and Stringi (2011) reported no difference in DM yield when berseem clover (Trifolium alexandrinum L.) was harvested either at 3 or 6 cm DI. There is also conflicting information regarding the impact of intensity of defoliation (DI; height at which plants are cut) on regrowth.…”
Section: Introductionmentioning
confidence: 90%